“Aplicación de interacción sin contacto en estimulación temprana a niños en edades no escolares” - Alarcón Bermúdez, María Mercedes (2018)
Early stimulation is an aspect of great importance for the development of children in their first years of life, and that could be supported with the use of ICTs. However, currently there have not been developed methods and technological processes focused on it as a mechanism to acquire knowledge in an unforced and fun way for children who are in nonschool ages. which makes it difficult for professionals to use applications and/or devices that could contribute to achieve agility, skills and mental and physical development. This work analyzes the use of applications based on contactless interaction to support the process of early stimulation in children of non-school age. For this purpose, a three-stage research was developed. In the first one, an exploration was carried out to know the behavior of the minors when having their first experience with an application of the proposed type, therefore a prototype was developed with this style of interaction. Secondly, specialists and parents were interviewed to determine necessary aspects to include in a better elaborated prototype to support early stimulation. Finally, once the behavior of the children and the opinions of the professionals were known, we proceeded to design a prototype consisting of several tasks to be used in a new study of users, which in turn allowed to know the reception of the proposal. The results obtained from the studies were favorable. In particular, the first study showed that children can respond positively to the selected interaction style. Then, in the final study this could be confirmed, by using the prototype focused on early stimulation. In this study the percentage of correct answers of the required actions was greater than or equal to 50%, which can be considered acceptable. In addition, parents and professionals related to early stimulation agreed on the utility of the proposal. It can be concluded that this style of interaction can support the process of early stimulation, allowing children to learn in a fun way, opening the way to future work related to this topic. Keywords: contactless interaction, early stimulation, telerehabilitation, natural user interface, NUI.